SMART APPLICATION FOR AUTISM DIAGNOSIS IN TODDLERS USING THE NAIVE BAYES METHOD IN LANGKAT REGENCY - Ryan Dhika Priyatna; Nababan, Arif Hamied; Nababan, Adli Abdillah; Miftahul Jannah; Harry Pratama Figna (INFOKUM, 2022)
All parents expect to have healthy, proud, and perfect children, however, sometimes things don't go the way they want. Some parents get the child they want and some don't. Some of them have children with special needs, such as autism. In Indonesia, each year, children with autism continue to increase. In 2015, it is estimated that there are approximately 12,800 children with autism and 134,000 children with the Autism spectrum in Indonesia. In addition to the lack of information and knowledge, preconceived notions also make parents reluctant to hand over their children for treatment. This research is motivated by the lack of solutions offered to existing problems by utilizing the development of information technology. The rapid development of technology in Indonesia has contributed a lot to the problems experienced by society with the birth of various kinds of smart systems. The development of a smart system based on an expert system can be a solution to the diagnosis of autism that appears in toddlers. The expert system that is offered is a system that can diagnose autism in toddlers in the Langkat district by implementing a method that can make decisions by providing the best solution. A good method is a method that has a high level of accuracy. The method used in this study is the Naive Bayes method where this method has been proven to be able to solve complex problems by predicting existing probabilities.